Frontoamygdala hyperconnectivity predicts affective dysregulation in adolescent moderate-severe TBI - Kevin C. Bickart; Kevin C. Bickart; Alexander Olsen; Alexander Olsen; Alexander Olsen; Emily L. Dennis; Talin Babikian; Talin Babikian; Ann N. Hoffman; Aliyah Snyder; Aliyah Snyder; Christopher A. Sheridan; et al. (Frontiers Media S.A., 2023)
In survivors of moderate to severe traumatic brain injury (msTBI), affective disruptions often remain underdetected and undertreated, in part due to poor understanding of the underlying neural mechanisms. We hypothesized that limbic circuits are integral to affective dysregulation in msTBI. To test this, we studied 19 adolescents with msTBI 17 months post-injury (TBI: M age 15.6, 5 females) as well as 44 matched healthy controls (HC: M age 16.4, 21 females). We leveraged two previously identified, large-scale resting-state (rsfMRI) networks of the amygdala to determine whether connectivity strength correlated with affective problems in the adolescents with msTBI. We found that distinct amygdala networks differentially predicted externalizing and internalizing behavioral problems in patients with msTBI. Specifically, patients with the highest medial amygdala connectivity were rated by parents as having greater externalizing behavioral problems measured on the BRIEF and CBCL, but not cognitive problems. The most correlated voxels in that network localize to the rostral anterior cingulate (rACC) and posterior cingulate (PCC) cortices, predicting 48% of the variance in externalizing problems. Alternatively, patients with the highest ventrolateral amygdala connectivity were rated by parents as having greater internalizing behavioral problems measured on the CBCL, but not cognitive problems. The most correlated voxels in that network localize to the ventromedial prefrontal cortex (vmPFC), predicting 57% of the variance in internalizing problems. Both findings were independent of potential confounds including ratings of TBI severity, time since injury, lesion burden based on acute imaging, demographic variables, and other non-amygdalar rsfMRI metrics (e.g., rACC to PCC connectivity), as well as macro- and microstructural measures of limbic circuitry (e.g., amygdala volume and uncinate fasciculus fractional anisotropy). Supporting the clinical significance of these findings, patients with msTBI had significantly greater externalizing problem ratings than healthy control participants and all the brain-behavior findings were specific to the msTBI group in that no similar correlations were found in the healthy control participants. Taken together, frontoamygdala pathways may underlie chronic dysregulation of behavior and mood in patients with msTBI. Future work will focus on neuromodulation techniques to directly affect frontoamygdala pathways with the aim to mitigate such dysregulation problems.